Applying utilization-focused evaluation to high school hazing prevention: A pilot intervention. (August 2019) - Hakkola, Leah; Allan, Elizabeth J.; Kerschner, Dave
Highlights: Utilization-Focused Evaluation enhanced stakeholder involvement. Results indicated intervention enhanced hazing and hazing prevention knowledge. Utilization-Focused Evaluation was a feasible approach for high school contexts. Continuous stakeholder involvement was key to addressing intended use of results. Abstract: Researchers argue that hazing can contribute to an abusive school climate and interfere with a positive learning environment for students. National efforts exist for establishing policies, protocols, evaluation, and education for students, administrators, and staff to prevent hazing at the college level, but this work has yet to be applied broadly in a high school context. In response to this gap, researchers implemented a pilot project at two high schools in Maine that consisted of hazing prevention training and assessment. This paper discusses the design, methods, and lessons learned through this collaborative, utilization-focused, and mixed-method training and evaluation with school personnel and high school student participants.